Flora of Ferruginous Outcrops Under Climate Change: A Study in the Cangas of Carajás (Eastern Amazon) - Giannini, Tereza Cristina; Acosta, André Luis; Costa, Wilian França; Miranda, Leonardo; Pinto, Carlos Eduardo; Watanabe, Maurício Takashi Coutinho; Zappi, Daniela Cristina; Giulietti, Ana Maria; Imperatriz-Fonseca, Vera Lucia (Frontiers in Plant Science, 2021)
Climate change has impacted biodiversity, altering the geographical distributions of species and their interspecific interactions. This study aims to evaluate the impact of climate changes on the flora of naturally open areas on ferruginous (canga) outcrops in the eastern Amazon and on interactions with their main functional pollinator group through pollination syndromes. We evaluated 608 plant species of two protected areas located in the eastern Amazon Biome. We classified each plant species into eight pollination syndromes. We estimated the effects of climate change on each species using species distribution modelling. Then we analyzed our results building ensemble models for each type of pollination syndrome. Most the plant species will potentially face reduction of suitable habitats and the scenarios showed that 42% of them may not find suitable areas in the study area. We found no significant difference between pollination syndromes related to the potential effect of climate change. The most climatically stable areas are those to the north and west of the state of Pará. Plant species of outcrops in eastern Amazon can be severely affected by climate change, independently of their main functional pollinator group. Urgent strategies for protecting species and their interactions are necessary.